Economic Analysis of Cluster Bean under Teak based Agroforestry System - Govind, V. M. Prajapati, M. B. Tandel, N. K. Patel, Y. A. Garde, Subhaprada Behera, David Camus (Archives of Current Research International, 2024)
Agroforestry systems (AFs) maintain biodiversity and provide valuable services by promoting ecological, social, and economic stability. Quantification of agroforestry system economics is associated with farmer’s livelihood. Considering this, the present study was carried out at Navsari Agricultural University, Navsari, Gujarat. The experiment was laid out in Randomized Block Design with Factorial concept consisting of 3 factors having 2 level each viz., varieties of cluster bean, foliar application of micronutrient iron and foliar application of micronutrient zinc on cluster bean grown separately under teak based agroforestry system and in open condition. The study has reported the economics of cluster bean which was grown under teak based agroforestry system and open condition. Further, economics was carried out for the cluster bean teak based agroforestry system as whole. The study has found that yield of cluster bean crop provided higher net return and BC ratio with variety Pusa Navbahar and foliar application of iron and zinc, when grown in open condition and under agroforestry system. In comparison to open condition, teak based agroforestry system as whole was found superior in terms of economically feasible.